Subcutaneous Fat Area Can Be as a Predictors of Drainage Volume After Lobectomy for Lung Cancer - Jie Xu; Shuai Yuan; Xiaopeng An; Jie Dong (Thoracic Cancer)
ABSTRACT Objective Currently, no uniform standard exists for the maximum drainage volume permitting chest tube removal following lobectomy in lung cancer patients, and limited research has explored factors influencing postoperative drainage. This study aimed to investigate the relationship between subcutaneous fat area (SFA) and postoperative drainage volume. Methods We conducted a retrospective analysis of 509 lung cancer patients who underwent video‐assisted thoracoscopic lobectomy. Clinical characteristics, postoperative outcomes (length of stay, hospitalization expenses), blood parameters, chest tube duration, 3‐day postoperative drainage volume, and SFA were recorded. Predictive factors for drainage volume were identified using univariate and multivariate logistic regression analyses. SFA was measured at the level of the 12th thoracic vertebra cross‐section using preoperative CT imaging. Results The analysis revealed significant positive correlations between chest tube duration and both length of stay (p < 0.001) and hospitalization expenses (p < 0.001). Chest tube duration (< 3 vs. ≥ 3 days) was primarily determined by 3‐day postoperative drainage volume (574 ± 252 vs. 885 ± 362 mL; p < 0.001). Univariate analysis demonstrated that 3‐day postoperative drainage volume correlated with age (p < 0.001), gender (p = 0.002), pathological type (p < 0.001), diabetes (p = 0.026), hypertension (p = 0.011), and SFA (p < 0.001). Multivariate logistic regression confirmed that age ≥ 65 years (p = 0.016), small cell lung cancer (SCLC; p = 0.022), and SFA ≥ 100 cm2 (p = 0.005) were independently associated with postoperative drainage volume ≥ 650 mL. Conclusions SFA significantly correlated with 3‐day postoperative drainage volume and may serve as a predictor for drainage volume following lobectomy in lung cancer patients. This association highlights its utility in guiding chest tube removal timing and potentially reducing the risk of pleural effusion recurrence.